Heat Treatment of Irradiated Graphite in an Oxidizing Atmosphere - Bespala E. V. Evgeniy (Evgeny) Vladimirovich; Pavlyuk (Pavliuk) A. O. Aleksander Olegovich; Kotlyarevsky S. G. Sergey Gennadjevich; Novoselov I. Yu. Ivan Yurievich; Bespala Y. R. Yuliya Rashidovna (2018, 2018)
Title screen